Generating new directions for reducing dog and koala interactions: a social marketing formative research study. Issue 2 (3rd April 2019) - Rundle-Thiele, Sharyn; Pang, Bo; Knox, Kathy; David, Patricia; Parkinson, Joy; Hussenoeder, Felix
ABSTRACT: Koala populations are declining. Conservation of this Australian icon requires a whole of community approach. To effect change, researchers and practitioners must effectively engage the target community, be open to different ways of thinking, and be receptive to new ideas and directions that match the times. This article reports the application of social marketing to decrease dog and koala interactions. A comprehensive program of formative research including a systematic literature review, expert interviews, online surveys and co-design sessions were employed to identify novel ideas and audience-focused strategies that can be applied to reduce dog and koala interactions. Results indicate that dog owners seek a non-koala focussed, dog training program that shows them what to do and a targeted approach alerting them to koala presence in addition to education and awareness efforts favoured by experts. This study indicates the need for more human centred research, which has been absent to date, given identified incongruence between expert and community views. We propose that audience-focused behaviour management strategies will, in turn, increase target audience adoption, campaign reach and promote effective community engagement with programs.